Association of Left Ventricular Diastolic Dysfunction With Cardiovascular Outcomes in Patients With Pre-dialysis Chronic Kidney Disease: Findings From KNOW-CKD Study - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Oh, Kook-Hwan; Choi, Kyu Hun; Oh, Yun Kyu; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2022)
Background: The impact of left ventricular diastolic dysfunction (LVDD) on cardiovascular (CV) outcomes in patients with pre-dialysis chronic kidney disease (CKD) has been rarely unveiled. We here investigated the association of LVDD with CV outcomes and all-cause mortality in patients with pre-dialysis CKD. Methods: A total of 2135 patients with pre-dialysis CKD from KNOW-CKD cohort were dichotomized by absence or presence of LVDD, which was defined as the ratio of the early transmitral blood flow velocity to early diastolic velocity of the mitral annulus (E/e’) > 14. Results: Cox regression analysis revealed that LVDD was significantly associated with increased risk of composite CV events (adjusted HR 2.194, 95% CI 1.486 to 3.240) and all-cause mortality (adjusted HR 1.830, 95% CI 1.168 to 2.869). Restricted cubic splines visualized stringent linear correlations of E/e’ with both composite CV events and all-cause mortality. In the sensitivity analysis only including the subjects with left ventricular ejection fraction ≥ 50%, LVDD was still significantly associated with adverse CV outcomes (adjusted HR 1.984, 95% CI 1.325-3.000) and all-cause mortality (adjusted HR 1.727, 95% CI 1.083 to 2.754), suggesting the impact of LVDD on the outcomes in patients with CKD is independent of LV systolic function. Subgroup analyses revealed that the associations were not modified by various clinical contexts, such as age, sex, burden of comorbid conditions, body mass index, estimated glomerular filtration rate, and albuminuria. Conclusions: LVDD is independently associated with adverse CV outcome and all-cause mortality in patients with pre-dialysis CKD.